Effect of Azadirachta Indica Extract On Hepatocarcinogenesis-Induced Rats - Elhassan Taha, Manal Mohamed (2007)
The effects of 5% A. indica aqueous extract (AI), or more commonly as Neem, on hepatocarcinogenesis induced Spraque-Dawley male rats were investigated. Hepatocarcinogenesis was induced in rats by employing a two carcinogen system: an intraperitoneal injection of 200 mg/kg diethyl nitrosamine (DEN) as initiator; followed by 0.02% of 2-acetylaminofluorene (AAF) in rat chow for two weeks to promote carcinogenesis. The rats were then left for two weeks to allow hepatic preneoplastic lesions to occur. The plant extract was prepared in 5% w/v in distilled water. Fresh leaves were collected, blended and mixed with distilled water. Twenty male rats Spraque-Dawley weighmg 150-250g were acclimatized for 1 week before use. The rats were divided into four groups of five rats each. iii The groups were: DENIAAF-iduced rats (C), DENIAAF-iduced rats treated with 5% A. indica (CAI), normal control rats (N) and normal rats treated with 5% A. indica extract group (NAI). The rats in group N and NAI were not induced with cancer however were injected once intraperitoneally with corn oil and act as normal control. The plant extract was fed to CAI and NAI groups to study its effects on both cancer and normal groups, respectively. In this study several parameters were evaluated as means of determining the effects of A1 on DENIAAF-induced hepatocarcinogenesis in rats. Body and liver weight profiles, foremost, hepatic lesions were scored in rats induced with DENIAAF cacinogens especially in the portal and lobular regions of the liver sections examined for histology. Loss of normal cell organization was also observed once the hepatocarcinogenesis was induced. In addition to histological observations, the TUNEL Assay, liver antioxidant enzyme Glutathione S transferase (GS-T), Glutathione Peroxidase (GPx) in the serum and liver, tumor marker alpha-fetoprotein (AFP) in serum and molecular detection of AFP and albumin genes expressions were conducted. The observation of the lesion scoring have shown significant difference (p<0.05) between DENIAAF and normal control groups (N, NAI). Histologically there were sigruficant changes in the lesion scoring of the liver in portal and lobular region in DENIAAF induced group (C) compared to the DENJAAF treated with A.indica (CAI). TUNEL assay supported that there was more numbers of apoptotic cells in the liver of (CAI) group compared to(C) group. The liver enzymes (GST & GPx) activity was measured and the result for both glutathione Stransferase and glutathione peroxidase were sigruficantly (p<0.05) higher in the (C) compared to the other groups (CAI, N, NAI). This result revealed that A. indica extract could reduce the activity of liver and serum GPx and GST enzymes of rats during hepatocarcinogenesis. However, the results of body and liver weight profiles showed that the CAI group was not significantly different (pN.05) from N, C and NAI groups. Alpha fetoprotein (AFP), a notable liver tumor marker, level was measured. The DENIAAF induced group (C) showed the highest increase in AFP levels while in CAI group illustrated significant (pc0.05) decrease in AFP level. There was no significant (pM.05) difference between N, NAI and CAI group. Mokdar detection of gene expression was done by RT-PCR for a-fetoprotein and albumin specific genes. However, the expression of the AFP gene was observed only in DEN/AAF induced group (C). Albumin gene expression was observed in all the study groups C, N, NAI and CAI proving the hepatic nature of the studied tissue and used as a housekeeping control gene in the RT-PCR experiments. As a conclusion, A. indica (Neem) has revealed a chemopreventive capability by regressing the hepatacarcinogenesis induced by DENJAAF carcinogens. This capability can be seen from the modulating effects of the plant in the biological indicators used in this study which can encourage the researchers to consider the A. indica (Neem) for further on mechanism and toxicology study.